Stainless Steel Cyclic Voltammograms in Dioscorea Opposita Flour Media - Isana Supiah Yosephine Louise; Siti Marwati; S. Sulistyani; Heru Pratomo Al; Felix Arie Setiawan (Universitas Pendidikan Indonesia, 2021)
Improving the efficiency of hydrogen gas production in the water electrolysis process draws great attention from many scholars. To improve the efficiency of the process and reduction in the cost, stainless steel has been widely implemented in the industrial water electrolysis process. Electrolyte modification is also one of the methods to improve the water electrolysis process. The study used Dioscorea opposita tuber flour as a media addition in an alkaline solution. The efficiency of water electrolysis was evaluated by cyclic voltammetry. The result showed that the activity of the electrode and energy consumption were increased with values of 29 and 23%, respectively, by adding 3 g of the media. However, no media addition showed the lowest energy consumption regarding overpotential value. In general, the Dioscorea opposita tuber flour tends to cover the electrode and reduce the activity. Moreover, the utilization of wastewater from Dioscorea opposita flour industry is still beneficial to produce hydrogen gas instead of using freshwater.